The Level of Teaching Competencies for Mathematics Teachers of the Upper Basic Stage in the Directorate of Education of South Hebron - Arman, Ibrahim Moh’D; Shahateet, Intisar Mahmoud (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify competencies level of Mathematics teachers in Hebron governorate, The researchers adopted the descriptive methodology on a simple random sample, which included (175) teachers from both genders during the second semester in (2020/2021).The researchers built a questionaire to measure the teaching competencies of Mathematics teachers in Hebron governorate, consisted of (35) paragraph, the instrument validity and reliability was both verified, the reliability coefficient was (0.92).The results showed that the level of teaching competencies among Mathematics teachers for upper primary stage in Hebron governorate was high, with an average of (3.93), and standard deviation of (0.52).The results also revealed that there are no stasically significant differences in the teaching competencies among Mathematics teachers for upper primary stage in Hebron governorate due to the variables of gender, specialization, years of experience, and scientific qualification.In light of these results, the study recommends the necessity of adopting and strengthening all teaching competencies, holding training courses to familiarize teachers with new teaching methods, and conducting similar studies for various disciplines to give a more comprehensive perception of the reality of teachers’ performance and their possession of the necessary teaching competencies, and conducting studies to evaluate teachers’ performance from the students’ point of view.
Keywords: Competencies; Teaching Competencies